(untitled) (The Review of Diabetic Studies, 2024)
Background: The expanding use of diabetes-associated weight-loss pharmacotherapy, particularly glucagon-like peptide-1 receptor agonists, has transformed metabolic disease management but has also introduced a growing spectrum of acute complications presenting to emergency departments. These complications often involve multisystem manifestations that challenge traditional, discipline-specific emergency care models. Objective: This study aimed to evaluate the preparedness of emergency and care coordination systems to manage complications related to diabetes-associated weight-loss pharmacotherapy and to develop a multidisciplinary management framework integrating medical secretarial coordination, nursing practice, X-ray imaging services, and patient care support. Methods: An integrative narrative review was conducted using peer-reviewed literature published between 2010 and 2024. Databases searched included PubMed, Scopus, Web of Science, and CINAHL. Clinical guidelines, systematic reviews, observational studies, and health systems research were synthesized thematically to identify common complications, system gaps, and multidisciplinary role contributions. The findings informed the development of a conceptual multidisciplinary emergency management framework. Results: The synthesized evidence demonstrated that complications associated with diabetes-related weight-loss pharmacotherapy frequently present as acute gastrointestinal, metabolic, renal, respiratory, and radiologically detectable conditions. Emergency outcomes were strongly influenced by system-level preparedness, particularly medication reconciliation accuracy, nursing-led early detection, timely access to diagnostic imaging, and effective administrative coordination. Fragmented care pathways were consistently associated with diagnostic delays and prolonged emergency department length of stay, whereas integrated multidisciplinary approaches were linked to improved patient safety and continuity of care. Conclusion: Emergency and care coordination systems are only partially prepared to address complications of diabetes-associated weight-loss pharmacotherapy. Implementing a multidisciplinary management framework that formally integrates administrative coordination, nursing assessment, diagnostic imaging, and patient care support may enhance emergency preparedness, reduce adverse outcomes, and improve patient-centered care in evolving healthcare systems.